Pelatihan Desain Produk Elektronik untuk Eksplorasi Kompetensi Pemuda Karang Taruna di Rt09/Rw04 Kelurahan Bulustalan Semarang - Rizqi Fitri Naryanto; Mera Kartika Delimayanti; Ari Dwi Nur Indriawan Musyono; Imanu Danar Herunandi; Aldias Bahatmaka (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
The Community Service Program carried out by the service team is to provide training to youth organizations, especially in RT09/RW09 Bulustalan Village, South Semarang District, Semarang City. Training in making electronic product designs in the form of posters, business cards, and calendars using Canva. The material's content has considered the needs of youth in today's internet era. Besides that, it can add value to the knowledge and skills of youth. From the results of the pre-test and post-test that have been carried out, it has been proven that this training is very beneficial for youth organization. The pre-test results show that less than 20% already know about the Canva module. Next, the post-test results show that more than 90% of the trainees are interested in and want to explore using Canva media. Positive responses have been given from the participants, showing that the training on making electronic product designs using Canva media benefits the participants.